Kinaray-a, 'Bandits,' Sulod-Bukidnon, 'Catholics,' 'Upright Farmers' social identity formation among a mountain people of Central Panay - German, Mary Acel D. (Department of Anthropology, College of Social Sciences and Philosophy, University of the Philippines Diliman, 2009)
The study looks into the formation of social identity among a mountain people in Valderrama, Antique in Central Panay. They have been attributed with a variety of identities i.e. Kinaray-a, 'Bandits', Sulod-Bukidnon and many other labels traced back from the colonial periods. Many of these labels were pejorative descriptions of the mountain peoples and wether they were valid or not they came to stereotype the mountain communities including the groups in Central Panay